Paradental cyst: Report of two cases - Kanno, Claudia M.; Gulinelli, Jessica L.; Nagata, Maria José Hitomi [UNESP]; Soubhia, Ana Maria Pires [UNESP]; Crivelini, Marcelo Macedo [UNESP] (Amer Acad Periodontology, 2006)
Background: the paradentat cyst is an odontogenic lesion of inflammatory origin that has few clinical signs and symptoms apart from recurring acute episodes. A well-defined radiolucency associated with the roots or distal to the crown may be seen radiographically. The purpose of this article is to report on different aspects of two cases involving paradental cysts. In the first case, the patient complained about recurring pericoronitis. A semilunar-shaped radiolucency on the distal aspect of the mandibular third molar was noted on the periapical radiograph. In the second case, the patient's main complaint was chronic trauma of the overlying mucosa. Radiographs revealed an enlarged pericoronal space.Methods: In both cases, the mandibular third molar was extracted due to a lack of space. Lesional samples were sent for histopathologic analysis.Results: In the first case, the drainage of cystic fluid and a regular concavity were found during tooth removal. In the second case, a nodular lesion was found adhering to the disto-buccal surface of the tooth arising from the distal wall of a periodontal pocket. The histopathologic analysis revealed a hyperplastic stratified squamous epithelium with arcading lining a fibrous capsule with inflammatory infiltrate, resulting in a final diagnosis of a paradental cyst.Conclusions: the presence of a paradental cyst should be considered when recurrent inflammatory periodontal processes are associated with partially erupted vital teeth, even when characteristic radiographic findings are absent. Definitive diagnosis requires a clinicopathologic correlation incorporating surgical, radiographic, and histologic findings.
Keywords: jaw cysts; odontogenic cysts; periodontal diseases